Self-confident analysis as a result of the love myself campaign by BTS - Cahyati, Siti; Fahriza, Irfan; Priatna, Ira Mirna; Purwanti, Isti Yuni (Universitas Negeri Yogyakarta, 2024)
The Korean wave or hallyu has evolved into a transnational phenomenon with global significance with the boy group named BTS being one of the leading representations in this wave of Korean cultural spread. Taking advantage of BTS's popularity as a public figure who has a significant social influence in shaping public opinion and behavior, BTS initiated the Love Myself campaign with UNICEF to spread positive messages, build confidence, respect for others, and end violence. This study aims to obtain a specific picture of the level of confidence as an influence of the Love Myself campaign conducted by BTS and UNICEF. The approach used in this study was a quantitative approach with a survey research design. Sampling in this study was carried out using a saturated sampling technique as the population was relatively small with 62 people . The results of the study showed that the majority of respondents felt that the Love Myself campaign had a positive impact on their lives. Based on quantitative data, the results were showed that in general the majority of respondents were in the medium category.The aspect of a positive outlook on self in the majority of respondents were in the high category. This explained that the